Efeito in vitro do óleo essencial de Cinnamomum zeylanicum Blume sobre Candida spp. envolvidas com infecções orais - Rangel, Marianne de Lucena (2016)
Introduction: Oral candidiasis is an opportunistic infection caused by yeasts of Candida genus. Evidence of increased microbial resistance stimulates the search of new strategies to prevent and treat this disease. Thus, the study of plants consists in a relevant therapeutic alternative, being Cinnamomum zeylanicum well investigated due the variety of biological activities proven, highlighting its antifungal effect. Objective: Evaluate the antifungal activity and mode of action of an essential oil (EO) extracted from Cinnamomum zeylanicum Blume leaves on Candida spp.. Material and Methods: The EO from C. zeylanicum Blume leaves had the phytochemical profile determined by Gas Chromatography coupled to Mass Spectrometry. Minimal Inhibitory Concentration (MIC) and Minimum Fungicidal Concentration (MFC) were determined on reference strains of Candida spp. (ATCC and CBS) and clinical strains collected from oral cavity, by microdilution technique and subculture, respectively. The sorbitol and ergosterol assays were performed in order to determine whether the EO interacts directly on the cell wall structure or modify the cell membrane ionic permeability. The growth inhibition kinetics of C. albicans in contact with EO in the MIC, MIC 2 and MIC 4 for 0h, 1h, 2h, 6h, 8h, 12h and 24h, were evaluated. Finally, was evaluated the effect of EO on the formation and reduction of Candida spp. biofilms. Nystatin, caspofungin or amphotericin B were used as positive controls and the culture medium, substance and vehicle were the negative controls. Data were statistically treated (Kruskal-Wallis, Dunn´s post hoc, a = 0,05). Results: The EO from C. zeylanicum Blume leaves has 26 components, with eugenol being the major component. It demonstrates to have fungicidal activity, with MIC and MFC values ranged from 62.5 to 1000 µg/mL. With regard to the mode of action, the antifungal activity of C. zeylanicum Blume EO seems to be related to fungal cell wall biosynthesis pathways. The kinetics assay demonstrated that the antifungal activity of EO in the MIC occurs in 24h and in the CIMx2 and CIMx4 in 8h of contact. The EO 500 µg/mL concentration inhibited the formation of mono- and multi-species biofilms of Candida spp., with reductions ranging from 34.94% to 49.42%. The same concentration caused reductions of the mature biofilm ranging from 50.18%-63.62% (24h of EO action) and 30.2%-59.26% (48h EO action). Conclusions: The EO from C. zeylanicum Blume leaves has eugenol as the major component, demonstrated antifungal activity on planktonic cells and biofilms of Candida spp. and act on cell wall biosynthesis pathways.